Optimization of meropenem dosing regimens in critically ill patients with augmented renal clearance - Luo, Jinfeng; Liu, Jing; Lin, Hongfu; Yang, Yang; Chen, Caihong; Chen, Jianping; Zhong, Han; Zhang, Shipao (Frontiers in Medicine, 2025)
The pharmacokinetics of meropenem are significantly altered in patients with augmented renal clearance (ARC), resulting in suboptimal plasma concentrations. The objective of this study is to investigate the efficacy of different meropenem regimens in critically ill patients with ARC. To this end, Monte Carlo simulations were conducted. The probability of target attainment (PTA) and the cumulative fraction of response (CFR) were evaluated with consideration of the minimal inhibitory concentration (MIC) breakpoint according to the Clinical and Laboratory Standards Institute (CLSI). The findings of this study demonstrate that meropenem administered at a dosage of 2 g every 8 h (q8 h) 2/3 h to critically ill patients with ARC [creatinine clearance (CrCL) of 140–200 mL/min] results in ≥ 90% PTA (100% fT > MIC) for lower MICs (≤ 2 mg/L). However, for higher MICs (4–8 mg/L), the administration of intensified regimens (2 g q8 h 4/6 h or continuous infusion) was necessary. The CFR analysis confirmed ≥ 90% target attainment for Klebsiella pneumoniae with regimens meropenem 2 g q8 h 2–6 h or continuous infusion, but not for Acinetobacter baumannii or Pseudomonas aeruginosa, regardless of regimen. For resistant Klebsiella pneumoniae (4 < MIC ≤ 8), prolonged (4–6 h) or continuous infusions are recommended. For Acinetobacter baumannii and Pseudomonas aeruginosa, alternative or combination therapies are advised due to insufficient PK/PD target attainment with meropenem monotherapy. The findings emphasize the importance of individualized dosing strategies in ARC patients, considering meropenem’s distinctive PK/PD characteristics, the pathogen’s MIC, and renal function, in order to effectively manage resistant Gram-negative infections while optimizing clinical outcomes.